Diachronic clues to synchronic grammar - Fuss, Eric; Trips, Carola (Linguistik aktuell, 2004)
This volume emphasizes a new line of thinking in generative grammar which acknowledges that certain synchronic properties of languages can only be fully understood if diachronic data is taken into consideration. The central topics addressed in this collection of papers are (1) a critical assessment of the hypothesis that certain apparently synchronic generalizations are actually the result of the mechanisms of language change, (2) an inquiry into how diachronic data can be used to evaluate and shape formal analyses of particular synchronic phenomena. Reviving the interest in diachronic explana.